Digital Employment Contracts and Legal Protection for Marketing Freelancers in Indonesia - Noor Shabiha Rahmawaty; Hardian Iskandar (JURNAL USM LAW REVIEW, 2025)
The rapid expansion of Indonesia's digital economy has introduced new contractual models that blur the legal distinction between employees and independent freelancers, creating uncertainty in the enforcement of rights and obligations. This study examines the legal construction of digital employment contracts between companies and digital marketing freelancers and analyzes the adequacy of legal protection mechanisms under Indonesian civil law. Employing a normative juridical approach with statutory and conceptual analysis, this research evaluates the Civil Code (particularly Article 1320), Law No. 11/2008 on Electronic Information and Transactions, Law No. 6/2023 on Job Creation, Law No. 27/2022 on Personal Data Protection, and Law No. 28/2014 on Copyright. The study finds that the validity and enforceability of digital employment contracts depend on compliance with Article 1320 of the Civil Code and Law No. 11/2008, supported by fair dispute resolution and data protection clauses. However, legal protection for digital marketing freelancers remains fragmented, lacking comprehensive integration of employment law, intellectual property rights, and social security provisions. This study contributes by integrating multiple legal dimensions of employment law, copyright, and data protection into a coherent analytical framework for freelancer protection, offering a foundation for developing adaptive Digital Labor Law in Indonesia's platform-based economy.